Physiological and psychological effects of wooden materials used in sustainable alternative living spaces on human health - Güler, İsmail Derda; Tor, Önder (Mobilya ve Ahsap Malzeme Arastirmalari Dergisi, 2024)
Regional population growth, depletion of natural resources, and environmental problems have caused people to rapidly turn to mobile spaces that consume less energy and are environmentally friendly living spaces. These mobile spaces should be designed within the scope of sustainability principles and offer innovative solutions. Elements such as energy efficiency, renewable energy sources, use of recyclable and sustainable materials, modular and flexible design, minimalist life and optimum the use of compact space, adaptation to climate and environmental conditions, social and economic sustainability, portability and low environmental impact are essential in the design and production of sustainable mobile living spaces. Wood is a natural, renewable, and sustainable material that solves these requirements. When evaluated in terms of physiological health, the thermal balance of wood material, moisture-regulating properties and natural fibre structure, and its harmony with the human body are the reasons for preference. Regarding psychological health, the natural atmosphere it creates in interior spaces, its stress-reducing, relaxing and peaceful effects, its air quality-improving properties, and low volatile organic compound emissions have positive effects. This study investigated the physiological and psychological effects of using wood, a frequently preferred living material in designing and producing mobile spaces with sustainable alternative living spaces suitable for road transportation and transport, on human health.
Keywords: Furniture; Mobilite Life; Caravan; Tinyhouse; Orman Endüstri Mühendisliği (Diğer); Forest Industry Engineering (Other); Mobilya; Mobil Yaşam; Karavan; Tinyhouse